The inflation targeting as a nominal anchor in South African monetary policy: Does the monetary policy becomes more effective? - Umar, Mohammed; Dahalan, Jauhari; Azman Aziz, Mukhriz Izraf (2015)
The paper investigates whether the South African Inflation Targeting (IT) framework has performed the role of the nominal anchor in the economy or not as well as the process through which the monetary authority determine its monetary instrument in the economy. Using the Generalized Method of Moments (GMM) estimators, the baseline and augmented forward-looking monetary policy rules were estimated for the pre, post-IT adoption and full sample periods. The findings vary across regimes.The result prior to the adoption of the IT framework does not follow the IT principles, whereas that of the post IT adoption and full sample periods are characterized as a forward-looking IT rule.The paper further uses the augmented monetary policy rule to identify the factors that determine the monetary policy instrument in South Africa.The results confirm that the South African monetary economy practiced full-pledged IT principle immediately after the adoption of the IT framework and that the monetary policy rule serve as a nominal anchor for the South African economy.The policy implication is that the South African Reserve Bank should further strengthen the IT framework adopted in the economy in order to continue keeping inflation to the required single digit target.